Structure, regulation and related diseases of the actin-binding protein gelsolin. (30th January 2019) - Feldt, Jessica; Schicht, Martin; Garreis, Fabian; Welss, Jessica; Schneider, Ulrich W.; Paulsen, Friedrich
Abstract: Gelsolin (GSN), one of the most abundant actin-binding proteins, is involved in cell motility, shape and metabolism. As a member of the GSN superfamily, GSN is a highly structured protein in eukaryotic cells that can be regulated by calcium concentration, intracellular pH, temperature and phosphatidylinositol-4, 5-bisphosphate. GSN plays an important role in cellular mechanisms as well as in different cellular interactions. Because of its participation in immunologic processes and its interaction with different cells of the immune system, GSN is a potential candidate for various therapeutic applications. In this review, we summarise the structure of GSN as well as its regulating and functional roles, focusing on distinct diseases such as Alzheimer's disease, rheumatoid arthritis and cancer. A short overview of GSN as a therapeutic target in today's medicine is also provided.